Pengaruh Lingkungan Kerja , Budaya Kerja, dan Beban Kerja terhadap Kinerja Karyawan pada PT. Anugerah Sinar Mustika (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to identify and analyze the influence of Work Environment, Organizational Culture, and Workload on the employee performance at PT. Anugerah Sinar Mustika Medan. The research method employed by the authors is a quantitative descriptive approach. The sample consists of all employees at PT. Anugerah Sinar Mustika Medan, totaling 69 individuals. Based on the results of the t-test, it can be concluded that the Work Environment, Organizational Culture, and Workload each have a partially significant effect on employee performance. Furthermore, the results of the F-test indicate that the Work Environment, Organizational Culture, and Workload simultaneously have a significant effect on employee performance. The coefficient of determination analysis shows an Adjusted R Square value of 0.733 (73.3%), which means that 73.3% of employee performance is influenced by the Work Environment, Organizational Culture, and Workload, while the remaining 26.7% is explained by other variables not examined in this study.